Bone Scanning in the Adductor Insertion Avulsion Syndrome - Madhuri Mahajan (World Journal of Nuclear Medicine)
A thigh splint (adductor insertion avulsion syndrome) is a relatively uncommon diagnosis analogous to shin splints. This article reports a 19-year-old female patient NOT a regular athlete who presented with groin pain. Physical examination was non-specific; magnetic resonance imaging pelvis did not reveal any abnormality. Patient referred for whole body bone scan, especially to locate any abnormality in the spine. This study highlights the role of whole body bone scan in the evaluation of groin pain and importance of evaluation of whole lower extremity.